2015
DOI: 10.1002/jtr.2038
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Implications of Virtual Reality Technology in Tourism Marketing: An Integrated Research Framework

Abstract: The proliferation of the Internet and other technological innovations has transformed the structure of the tourism industry as well as affected how tourism destinations are perceived and consumed. The 3D virtual world provides opportunities for destination marketing organizations to communicate with targeted markets by offering a rich environment for potential visitors to explore tourism destinations. However, as of yet, there is little understanding about how to effectively market tourism destinations to virt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
267
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(342 citation statements)
references
References 139 publications
15
267
0
9
Order By: Relevance
“…The first theme of mobile technology in tourism that is attracting researchers' interest is short range wireless technology such as Radio frequency identification (RFID) [97][98][99] and Near field communication (NFC) [67,76,77,100]. The second theme includes augmented reality [101][102][103][104] and virtual reality [105], which enables a pre-experience for a user [33]. This theme is noted in tourism research as tourism marketing tools [106].…”
Section: Smart Tourism From the Technology Perspectivementioning
confidence: 99%
“…The first theme of mobile technology in tourism that is attracting researchers' interest is short range wireless technology such as Radio frequency identification (RFID) [97][98][99] and Near field communication (NFC) [67,76,77,100]. The second theme includes augmented reality [101][102][103][104] and virtual reality [105], which enables a pre-experience for a user [33]. This theme is noted in tourism research as tourism marketing tools [106].…”
Section: Smart Tourism From the Technology Perspectivementioning
confidence: 99%
“…However, as of yet, there is little understanding about how to effectively market tourism destinations to virtual world participants who are technology users as well as potential consumers (Huang, Backman, Backman & Chang, 2016). Williams & Hobson (1995) pointed out that virtual reality, equipped with visualization components offering interactivity and immersion into a virtual experience in tourism, simulated environments that affect tourists" trip planning and influence the tourism industry.…”
Section: Costs and Incomes)?"mentioning
confidence: 99%
“…The result of Huang, Backman, Backman & Chang (2016) research on the effects of virtual reality technology in tourism marketing revealed that perceived usefulness is positively related to the experience of enjoyment, indicating that useful information in 3D tourism sites -such as the visual resemblance and overall feel of the physical tourism destination, naturalistic elements and images of cultural authenticity -can enhance the consumer experience of enjoyment.…”
Section: Costs and Incomes)?"mentioning
confidence: 99%
“…A partir del uso intensivo de las TIC en todos los ámbitos de la vida humana y por ende en el turismo, los estudios se han multiplicado en temáticas y abordajes, en dos grandes sentidos, el primero que abarca los estudios que se centran en el desarrollo de tecnología para su aplicación en el turismo (Gretzel, Fesenmaier, Formica & O'Leary, 2006) mediante sistemas expertos en lo que se ha denominado smart tourism (Buhalis & Amaranggana, 2013), mediante el aprovechamiento de la información, y cloud computing (Sheldon, 2004), el desarrollo de tecnologías para la optimización en el uso de los recursos en hoteles, aeropuertos y destinos turísticos (Buhalis & O'Connor, 2005), o de manera específica en las oficinas de congresos y convenciones (Yuan, Gretzel & Fesenmaier, 2006), en la mejoría de la información para uso de los visitantes en comunidades de redes sociales de viajeros (Lo & McKercher, 2015) y también para mejorar la experiencia de viaje mediante realidad aumentada y/o realidad virtual (Govers, 2005;Gretzel & Jamal, 2009;Huang, Backman, Backman, & Chang, 2015;Kounavis, Kasimati & Zamani, 2012).…”
Section: Marco Teóricounclassified